The Cocrystal of Ubiquinol: Improved Stability and Bioavailability - Qi Zhang; Mengyuan Xia; Chenxuan Zheng; Yinghong Yang; Junjie Bao; Wenjuan Dai; Xuefeng Mei (MDPI AG, 2023)
Coenzyme Q10 (CoQ10) exists in two forms, an oxidized form and a reduced form. Ubiquinol is the fully reduced form of CoQ10. Compared to the oxidized form, ubiquinol has a much higher biological absorption and better therapeutic effect. However, ubiquinol has an important stability problem which hampers its storage and formulation. It can be easily transformed into its oxidized form-ubiquinone-even at low temperature. In this work, we designed, synthesized, and characterized a new cocrystal of ubiquinol with vitamin B3 nicotinamide (UQ-NC). Compared to the marketed ubiquinol form, the cocrystal exhibited an excellent stability, improved dissolution properties, and higher bioavailability. The cocrystal remained stable for a long period, even when stored under stressed conditions. In the dissolution experiments, the cocrystal generated 12.6 (in SIF) and 38.3 (in SGF) times greater maximum ubiquinol concentrations above that of the marketed form. In addition, in the PK studies, compared to the marketed form, the cocrystal exhibited a 2.2 times greater maximum total coenzyme Q10 concentration and a 4.5 times greater AUC than that of the marketed form.